2012
DOI: 10.19173/irrodl.v13i2.1185
|View full text |Cite
|
Sign up to set email alerts
|

Developing and deploying OERs in sub-Saharan Africa: Building on the present

Abstract: Open educational resources (OERs) have the potential to reduce costs, improve quality, and increase access to educational opportunities. OER development and deployment is one path that could contribute to achieving education for all. This article builds on existing information and communication technology (ICT) implementation plans in Africa and on the experiences of organizations and initiatives such as the African Virtual University (AVU), OER Africa, the South African Institute of Distance Education (SAIDE)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…On the theme "survey", the publications provide results of the research carried out mainly on the "use" of OER as in the work of Wright and Reju (2012), about "reuse" as discussed in papers by Hanna and Wood (2011) and Petrides et al (2008) and as "shared" in the work of Rolfe (2012).…”
Section: Main Authors Abstract and Topics Addressed By The Publicationsmentioning
confidence: 99%
“…On the theme "survey", the publications provide results of the research carried out mainly on the "use" of OER as in the work of Wright and Reju (2012), about "reuse" as discussed in papers by Hanna and Wood (2011) and Petrides et al (2008) and as "shared" in the work of Rolfe (2012).…”
Section: Main Authors Abstract and Topics Addressed By The Publicationsmentioning
confidence: 99%
“…Strategies are ahead to get the selected MOOCs translated for Coursera 25 ; however the effectiveness of translation of language with no appropriate modifications might well hamper the overall accessibility of the learning resources. Translation of selected courses may also lead to the dominance of those translated subjects 26 . The language issue may be unintended; but it does pass on messages that can be considered to be valuable.…”
Section: Languagementioning
confidence: 99%
“…Some governments are taking initiatives to make available maximum internet access to people through the provision of cyber cafes and in terms of stimulating opportunities for extended study, to access cyber learning opportunities 26 . However, these still appear to remain limiting factors.…”
mentioning
confidence: 99%
“…It is interesting to note that extension was considered the most important reason for adopting OER in In the case of sub-Saharan Africa, developing and deploying OER in the resource-constrained countries can bring many benefits and the development and sharing of OER in higher education is being supported by several organizations such as the African Virtual University (AVU), OER Africa, the South African Institute of Distance Education (SAIDE), and the Teacher Education in SubSaharan Africa (TESSA) Project (Wright & Reju, 2012). It might therefore be concluded that where there is regional and national leadership, institutions may adopt OER more readily and provide organizational supports and faculty members may make greater use of OER.…”
Section: Regional Differencesmentioning
confidence: 99%